Antioxidant capacity of lactic acid bacteria isolated from marine fish and invertebrates of the province of Chubut, Patagonia, Argentina - Sosa, Franco M. (2023)
The antioxidant activity of lactic acid bacteria (LAB) has been studied in depth in strains isolated from terrestrial organisms and fermented or unprocessed foods; however, information on isolates of marine origin is still being determined. This feature is of particular interest due to its potential use in functional foods in this work. The antioxidant capacity of 16 bacteriocinogenic LAB isolated from marine organisms from the Chubut coast (2010-2022 period) was studied with in vivo and in vitro assays. The in vitro antioxidant capacity was assessed by reduction of 2,2-diphenyl-1-picrylhydrazyl (DPPH), cupric ion-reducing antioxidant capacity (CUPRAC), and hydroxyl radical scavenging in unlysed cells. Saccharomyces cerevisiae was used as a eukaryotic biological model to evaluate the protective effect in vivo. The antioxidant capacity results from the DPPH radical scavenging test exhibited values between 15-37.5%, while hydroxyl radical scavenging showed values between 13.3-61.9%, and, for the CUPRAC method, values varied between 0.223-0.551, equivalent to mmol of ascorbic acid per ml of cellular suspension. The LAB protective effect on the survival rate of S. cerevisiae displayed results between 36-90%. No relationship was established between the values obtained with the different methods or between members of the same genus or species; consequently, the antioxidant behavior could be considered strain-depend. Results suggest that the antioxidant capacity of bacteriocinogenic LAB of marine origin can be used as a metabolic selection trait with biotechnological potential in the development of functional foods.